Familial hemiplegic migraine type 2: a case report of an adolescent with ATP1A2 mutation - Zhang, Hui; Jiang, Li; Xian, Yuqi; Yang, Sen (Frontiers in Neurology, 2024)
This study presents a case report of a male adolescent diagnosed with familial hemiplegic migraine type 2 (FHM2), an autosomal dominant inheritance disorder caused by ATP1A2 mutation. We report the patient who presented with headache, aphasia, and left-sided weakness. Cerebrovascular disease and various infectious agents were unremarkable during the patient’s extended hospital stay. Our case revealed that brain hyperperfusion in familial hemiplegic migraine (FHM) persists over an extended duration, and despite the disease being in a state of recovery, enhanced brain magnetic resonance imaging (MRI) continues to exhibit hyperperfusion. A genetic testing was performed which revealed a mutation in the FHM2 gene (c.1133C > T). The patient has been followed for 3 years after hospital discharge. The boy suffered four episodes of hemiplegia and multiple episodes of headaches, and gradually developed seizures and cognitive impairment. It is advisable to consider FHM as a potential diagnosis for patients presenting with typical symptoms such as recurrent paroxysmal headaches and limb activity disorders.